Peces óseos comerciales del Parque Gorgona, Pacífico colombiano (Osteichthyes: Muraenesocidae, Hemiramphidae, Belonidae, Scorpaenidae, Triglidae, Malacanthidae, Gerreidae, Sparidae, Kyphosidae, Sphyraenidae e Istiophoridae) - Franke, Rebeca (1996)
Information about sixteen species of fishes of economical value from the Parque Nacional Natural Gorgona (Colombian Pacific) is presented. The reports of the doubtful scorpionfish, Pontinus dubius, the speckled scorpionfish, Pontinus sp., the Pacific fIagfin mojarra, Eucinostomus currani, and the Gorgona barracuda, Sphyraena sp., are remarkable, since they are recorded for the first time from Colombia; data on Colombian specimens of the longfin halfbeak, Hemiramphus saltator, are presented for the first time. The Pacific pikeconger, Cynoponticus coniceps, the fIat needlefish, Ablennes hians, the southero scorpionfish, Pontinus clemensi, the lumptail searobin, and the Pacific porgy, Calamus brachysomus, are new reports from Isla de Gorgona. Biological and fishery data are given about the goldeneye tilefish, Caulolatilus affinis, and the bluestriped chub, Sectator ocyurus; the status in Gorgona of the stone scorpionfish, Scorpaena mystes, the rainbow scorpionfish, Scorpaenodes xyris, the Cortez chub, Kyphosus elegans, the Galápagos barracuda, S. idiastes, and the Indo-Pacific sailfish, [stiophorus albicans, is discussed.